Catching the moon : the story of a young girl's baseball dream - Hubbard, Crystal (Lee & Low Books, 2005)
"A picture book biography highlighting a pivotal event in the childhood of African American baseball player Marcenia "Toni Stone" Lyle Alberga, the woman who broke baseball's gender barrier by becoming the first female roster member of a professional Negro League team"--Provided by publisher.